BRAF and KRAS mutations in papillary thyroid carcinoma in the United Arab Emirates. - Suhail Al-Salam; Charu Sharma; Bachar Afandi; Khaled Al Dahmani; Ali S Al-Zahrani; Amal Al Shamsi; Juma Al Kaabi (PLoS ONE, 2020)
Background Papillary thyroid carcinoma (PTC) is the most common malignant thyroid neoplasm comprising 80-90% of all thyroid malignancies. Molecular changes in thyroid follicular cells are likely associated with the development of PTC. Mutations in serine/threonine-protein kinase (BRAF) and Rat sarcoma viral oncogene homolog (RAS) are commonly seen in PTC. Methods In total, 90 cases of PTC are randomly selected from archive paraffin blocks and 10μm sections were cut and processed for DNA extraction. BRAF V600E mutation and 8 types of KRAS mutations were investigated using Real Time PCR. Results BRAF V600E mutation was identified in 46% of PTC while KRAS mutations were seen in 11% of PTC. There was significant correlation between BRAF V600E mutation and PTC larger than 5cm in diameter, positive surgical margin and lymph node metastasis. BRAF V600E mutation was significantly higher in patients with less than 55-year of age than those more than 55-year of age. BRAF V600E mutation was significantly higher in patients with family history of thyroid cancer than those without. There was no significant difference in BRAFV600E mutation between males and females, PTC classic and follicular variants, unifocal and multifocal PTC. There was a significant higher percentage of BRAF V600E mutation in classic PTC than papillary microcarcinoma variant. There was no significant age, gender, histologic type, tumor size, lymph node metastasis, tumor focality, and surgical margin status differences between KRAS mutated and non-mutated PTC. Conclusion BRAF V600E and KRAS mutation are seen in a significant number of PTC in the UAE. BRAF mutation is significantly correlated with large tumor size, positive surgical margins and lymph node metastasis suggesting an association between BRAF V600E mutation and tumor growth and spread.